Analyzing the Impact of Social and Cultural Factors on Interactions and Collaboration among Health Administration Specialists, Health Assistants, and Other Healthcare Providers in Primary Care Centers in Saudi Arabia - Abdulrahman Mohsen Alharbi,; Abdullah Zaal Asri Aldhafeeri,; Fayez Fahs Awaid Aldhafeeri,; Khalid Malouh S Aldhafeeri,; Radhi Malouh S Aldhafeeri,; Taleb Daham Abar Al Dhafeeri, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Saudi Arabia's primary healthcare system involves complex interactions between health administration specialists, health assistants, and other healthcare providers. This study analyzes how social and cultural factors influence these professional relationships and collaborations. Key factors examined include gender segregation, collectivistic orientations, power distance, and Islamic values. A mixed-methods approach was employed, combining surveys of 500 primary care staff with in-depth interviews of 25 health administrators, assistants, and clinicians. Findings indicate that segregated work spaces and collectivistic orientations promote strong in-group bonds, while large power distances can hinder open communication between lower and higher-status staff. Islamic values provide a shared ethos of compassion and service. Targeted diversity training, inclusive team-building initiatives, and culturally-informed leadership approaches are recommended to optimize collaboration while respecting Saudi norms.